Sustainable nanomaterials for energy applications - Cremades, Ana; Maestre, David (IOP Publishing, 2023)
Recent progress in functional materials is driven by the global need for more sustainable technological developments and the obtainment of clean and affordable energy while maintaining the demanding standards of high-performance devices. The development of nanomaterial oxides is an active research area with meaningful applications in energy generation, transformation and storage. This comprehensive book covers the latest research on sustainable nanomaterials for energy applications. The book covers fundamental and applied issues, such as selected synthesis techniques for nanomaterials and their development in applications covering the generation, storage and transformation of energy. The book is a valuable reference text for researchers in the nanotechnology, oxides and energy fields. Readers will benefit from a complete perspective not only of the materials and applications but of other considerations in the context of sustainability.
Keywords: Nanostructured materials.; Renewable energy sources -- Technological innovations.; Clean energy -- Technological innovations.; Materials science.; TECHNOLOGY & ENGINEERING / Materials Science / General.; elektronické knihy; electronic books